Magnet Design by Integration of Layer and Chain Magnetic Systems in a π‐Stacked Pillared Layer Framework1. (24th November 2014) - Fukunaga, Hiroki; Miyasaka, Hitoshi
Abstract The control of inter‐lattice magnetic interactions is a crucial issue when long‐range ordered magnets that are based on low‐dimensional magnetic frameworks are designed. A "pillared layer framework (PLF)" model could be an efficient system for this purpose. In this report, A magnet based on a π‐stacked PLF with a phase transition temperature of 82 K, which can be increased to 107 K by applying a pressure of 12.5 kbar, is rationally constructed. Two types of low‐dimensional magnetic framework systems, an electron donor/acceptor magnetic layer and a charge transfer [FeCp*2]+TCNQ.− columnar magnet ([FeCp*2]+=decamethylferrocenium; TCNQ=7, 7, 8, 8‐tetracyano‐p‐quinodimethane), are integrated to fabricate the magnet. This synthetic strategy employing a combination of layers and chains is widely useful not only for magnet design, but also for the creation of multifunctional materials with pores and anisotropic frameworks.